The role of spine curvatures in the sagittal plane in physical performance among team sports players - Kozlenia, D.; Kochan-Jachec, K.; Domaradzki J. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Spine shapes determine the body posture, which could also be impacted by specific sports training. However, the meaning of spine curvatures in physical performance remains unclear. This study aimed to investigate the role of spine curvatures in the sagittal plane in physical performance regarding team sports training. METHODS: The study sample included 21±2.1 years old males: 19 team sport players (TSP) and 17 average physically active men (comparison group, CG). The spine curvatures in the sagittal plane were assessed using the photogrammetric method (Moire), and physical performance tests were conducted. RESULTS: The sacrolumbar spine position was positively related to speed abilities only in TSP. The sacrolumbar spine inclination angle (a) increase by one unit was associated with improving the time in the 20 m linear speed and agility t-test measured change of direction speed (CODs) by 0.02 s and 0.07 s, respectively. The downsized lumbar lordosis angle by a one-unit caused improvement by 0.01s in 20 m linear speed. In CG, it was revealed that a higher thoracolumbar spine inclination angle (ß) was associated with a worse ability to maintain static balance. In TSP, sacrolumbar spine position is associated with speed abilities. CONCLUSIONS: The flattened spine curves are not conducive to linear speed and CODs. There is a need to keep proper spine curvatures to develop and maintain high physical performance. Indicated sagittal plane spine curvatures could predispose to better speed performance. Measurement of these parameters could be valuable in prediction speed and CODs abilities.